Research and application of spatial distribution law of additional compressive stress field in surrounding rock of bolt support - Yuantian SUN; Shang WANG; Guichen LI; Changliang HAN; Haoran HAO; Jinghua LI; Haisen ZHAO (Meitan xuebao, 2025)
The application of coal mine roadway bolt support has been widely adopted. The additional stress field due to the support action of the bolts on the surrounding rock is crucial for quantifying support parameters and optimizing support schemes. In order to study the influence of bolt (cable) related parameters on the spatial three-dimensional distribution of the additional compressive stress field of the surrounding rock, the mechanism of the additional compressive stress generated by the entrusted anchor force and the sticking anchor force of the surrounding rock under the action of the bolt was analyzed theoretically, and the additional compressive stress model of the surrounding rock was established, and the distribution characteristics of the additional compressive stress field were spatially characterized. Further, the correctness of the model is verified through simulations and theoretical comparisons. Using an additional stress threshold of ≥0.02 MPa in surrounding rock as a baseline, the research quantifies the key parameters of bolt (cable) support, namely, pre-tensioning force, length, and anchorage length, and their effects on the spatial distribution form, maximum diffusion radius, height (spacing), and volume of the additional stress field in surrounding rock. Under bolt support, as the pre-tensioning force increases, the distribution pattern of the spatial additional stress field transforms from a vertical “ellipsoid” to a horizontal “ellipsoid”. When the bolt length increases, the shape changes from an approximate “ellipsoid” to a “gourd shape”, and as the anchorage length increases, it transitions from a “gourd shape” back to an approximate “ellipsoid”. As the pre-tensioning force and length of the bolts increase, the radius, height, and volume of the additional stress field generated by the bolts increase, whereas the influence of the anchorage length on the additional stress field is the opposite. Under cable support, as the cable length increases, the spatial distribution of the additional stress field in the surrounding rock changes from an approximate “ellipsoid” to a “gourd shape”. When the cable length exceeds 5 m, it becomes two intermittent “ellipsoids” with a smaller upper part and a larger lower part, showing no significant change in distribution even with increases in pre-tensioning force and anchorage length. With increasing pre-tensioning force, the radius and volume of the additional stress field generated by cable support increase, while the spacing between the upper and lower stress fields decreases. As the cable length increases, the height of the additional stress field in the surrounding rock rises, subsequently becoming two intermittent stress fields, with increasing spacing, while the radius and volume of the stress fields first increase and then decrease. With the increase in cable anchorage length, the spacing of the additional stress field in the surrounding rock gradually decreases, with the radius initially increasing and then decreasing, and the volume showing little increase. The study further analyzes the effects of high/low additional stress on the roadway roof under the combined support of bolts (cables) based on some principles from composite beam and suspension theory, establishing calculation formulas for high/low thresholds. Comparing the volume size of the surrounding rock’s additional stress field helps determine the advantages and disadvantages of the bolt support scheme. The research subjects include the 21204 return airway of the Hulusulu Coal Mine and the transportation roadway of the Chengjiao Coal Mine LW21106 working face, analyzing the characteristics of the original/new support schemes and calculating the high/low stress thresholds and their total volume covering the roof of the two typical roadways. The results show that the optimized scheme with bolts (cables) can create an effective and continuous additional stress field in the roof, significantly increasing both the high and low stress field volumes and effectively controlling the deformation of the surrounding rock.